Taxonomic revision of Achradocera Becker (Diptera: Dolichopodidae), with description of two new species - Quevedo, Lucas; Capellari, Renato S.; Lamas, Carlos José E. (Zootaxa, 2024)
The New World genus Achradocera Becker, 1922 (Diptera: Dolichopodidae) is revised and includes the following 12 species: A. angustifacies Becker stat. rev. (= A. chilensis (Van Duzee) syn. nov. and A. edwardsi (Van Duzee) syn. nov.; Chile); A. apicalis (Aldrich) (Antigua, Dominica, Marquesas, Montserrat, St. Lucia, Tonga and French Polynesia); A. arcuata (Van Duzee) (western USA, Hawaii and Mexico); A. balin sp. nov. (Brazil); A. barbata (Loew) (eastern Canada and eastern USA); A. excavata (Van Duzee) (Bahamas, British Virgin Islands, Cuba, Dominican Republic, Jamaica and Puerto Rico); A. femoralis Becker (Colombia and Curaçao); A. gimli sp. nov. (Brazil, Bolivia and Trinidad and Tobago); A. insignis Parent (Brazil, Paraguay and Argentina); A. longiseta Parent (Argentina); A. meridionalis Becker (= A. contracta (Van Duzee) syn. nov. and A. shannoni (Van Duzee) syn. nov.; Mexico, Belize, Guatemala, El Salvador, Peru and Hawaii); and A. tuberculata (Van Duzee) (Brazil, Guyana, Trinidad and Tobago and Venezuela). All valid species and their diagnostic features are fully photographed, a key to males is provided and the known distribution of each species is mapped.